Technological Pedagogical Content Knowledge (TPACK) and Digital E-Scaffolding for Special School Teachers - Wiwik Widajati; Siti Mahmudah (Indonesia Approach Education, 2023)
21st century learning requires Special School teachers to have knowledge and skills in implementing technology-based learning strategies to facilitate and facilitate student learning and improve learning outcomes. This study aims to analyze the ability of Technological Pedagogical Content Knowledge (TPACK) and digital e-scaffolding in Special School teachers. This type of research used descriptive quantitative. The sample in this research is Special School teachers. Data collection using a questionnaire. Data analysis using descriptive statistics. The results showed that the ability of Special School teachers to integrate and utilize TPACK and computer and internet-based digital e-scaffolding for learning students with disabilities was in the good category. The results of this study show that 78% of Special School teachers have been able to utilize TPACK and digital e-scaffolding in learning for students with disabilities. TPACK skills and digital e-scaffolding are needed by Special School teachers to integrate and utilize technology that supports the learning of students with disabilities. The novelty of this research is to simultaneously analyze TPACK and e-scaffolding because much research has been done on TPACK but research on TPACK and digital e-scaffolding is still limited.